PROFILE OF RENAL FUNCTION LABORATORY EXAMINATIONS IN PROLANIS PATIENTS IN PONTIANAK CITY - Nuswantoro, Ari; Aprillia, Dinasti; Purwaningsih, Indah; Arifah, Rizki Zanuba (Jurnal Laboratorium Khatulistiwa, 2022)
Diabetes mellitus (DM) and hypertension is one of the chronic diseases that cause health problems in Indonesia. The government organizes a Management Program Chronic Disease (Prolanis) in order to manage patients with both of these diseases. One of the activities carried out is laboratory tests of urea and serum creatinine. This study aims to describe the number of DM and hypertension sufferers as well as serum urea and creatinine levels in Prolanis participants which checked themselves into the Unit Pelaksana Teknis Pusat Laboratorium Kesehatan Kota Pontianak. The study was conducted using a total sampling method by looking at the medical record data of Prolanis participants, who will check themselves to the Unit Pelaksana Teknis Pusat Laboratorium Kesehatan Kota Pontianak, from January – December 2021 so that data were obtained from 333 patients consisting of 84 men and 349 women with an age range of 26 – 91 years. The results showed that 163 patients were diagnosed with DM and the remaining 170 people suffered from hypertension. The average value of urea levels to male patients is 36.4 mg/dL (14 – 113 mg/dL) and to women it is 27.3 mg/dL (11 – 80 mg/dL). The average value of creatinine levels to men is 1.3 mg/dL (0.5 – 5.3 mg/dL) and to women is 0.8 mg/dL (0.4 – 1.9 mg/dL). Urea and creatinine levels are theoretically associated with the incidence of DM and hypertension.